Beyond Legal Constraints: Understanding Barriers to Humanizing Responses in the Aftermath of Hate Speech at Private Universities - Eliza Morse Bentley Epstein; Nicole Cruz Ngaosi; Noor Khalayleh; Liliana M. Garces; Jackie Pedota (MDPI AG, 2024)
Supreme Court rulings prevent public institutions from censoring hate speech for content-even if that content has damaging consequences for marginalized students and conflicts with other institutional objectives. This case study examines administrator responses to hate speech and impacts for racial inclusion at a private university unconstrained by First Amendment protections. The findings illustrate that, even in contexts where administrators have both the constitutional leeway to enact stricter speech policies and a deep investment in building an anti-racist community, normative understandings about freedom of expression hamper efforts for racial inclusion and humanizing responses. We propose an "inclusive freedom" approach that leverages norms of academic freedom as a path forward for postsecondary institutions to address harm in the aftermath of hate speech.